Comparação da mortalidade dos adventistas do sétimo dia com a população não adventista no período de 2003 a 2009 no estado do Espírito Santo - Velten, Ana Paula Costa (2013)
This study aimed to compare the mortality profile of Seventh-day Adventists with general population in the period 2003 to 2009 in the state of Espírito Santo, Brazil. This was a descriptive study that studied all deaths in the state during the period covered by separating them into two groups: Adventist and the general population.The separation was performed by searching the names of the deceased Adventists, provided by the administration of the church, in the state bank of Mortality Informations System. Groups of deaths were reported and distributed by the 10° chapter of the International Classification of Diseases. Was also checked the average years lived in groups and Standardized Mortality Ratios (SMR) and confidence intervals of 95%. The results show that Adventists die more often in older age groups relative to general population. The main causes of death for the Adventists were the circulatory diseases (34,45%), neoplasms (20,06%) and external causes (9,87%). For the general population the circulatory diseases were also the leading cause of death (31,70%), followed by external causes (18,57%) and neoplasms (15%). Adventists had 4.57 years on average over the years lived in the general population. The SMR of Adventists were 55,87 (40,99 74,38) for the circulatory diseases, 48,59 (24,3 86,84) for the respiratory diseases, 15,48 (7,31 28,76) for the digestive diseases, and 41,3 (20,91 73,18) for the external causes. It was concluded that although no one knows the extent of health recommendations adoption by the Adventist who died there is evidence that the recommendations have beneficially influenced the mortality profile of the same relative the general population.